Analysis of Operation and Marketing Strategies of Head Accounts on Social Platforms: a Case Study Based on RED Beauty Bloggers Under the ‘Grass-raising’ Recommend Model - Zhao, Yufan (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of online social media platforms, Social media platforms have become a powerful tool for brands to connect with consumers and promote their products, RED is one of the online social platforms that have sprung up with the development. RED has emerged as a model of product sharing and recommendation through 'planting and pulling weeds'. The purpose of this study is to analyze the operation and marketing strategies of beauty bloggers on RED under the mode of 'grass-raising'. This study analyzes the effects of various operational strategies by giving specific data and analyzes the specific operations of bloggers in 'grass-raising' recommendation mode through case studies. Thereafter, the problems of content homogenization and product cooperation selection in the operation of RED beauty bloggers were also raised, and corresponding solutions were given. Finally, it is concluded that RED beauty bloggers' operational strategy in 'grass-raising' recommendation mode is a very effective way of product recommendation, and the limitations of this study and the outlook for future directions are presented.